Biofarmakologi Seduhan Teh Telang Clitorea ternatia. L sebagai Obat Pengencer Dahak dan Antibakteri - Firmansyahh, M. Ali Ridho (Maliki Interdisciplinary Journal, 2025)
Butterfly flower extract (Clitoria ternatea L.) is a source of bioactive compounds such as flavonoids, tannins and saponins, which have been proven to have various pharmacological activities. This study aims to evaluate the effect of adding butterfly pea flower extract to tea in increasing its effectiveness as a mucolytic and antibacterial agent. The mucolytic test was carried out by analyzing the viscosity of the mucus solution, while the antibacterial activity was tested using the disc diffusion method against the pathogenic bacteria Staphylococcus aureus and Escherichia coli. Test results showed that tea with added telang extract was able to reduce mucus viscosity significantly compared to tea without extract, showing its potential as a natural mucolytic agent. In addition, the antibacterial activity of tea based on butterfly pea extract produced a wider zone of inhibition against both types of bacteria tested, indicating a synergistic effect from the combination of butterfly pea extract with tea components. The addition of this extract also does not significantly change the taste and aroma of the tea, so it still meets consumer preferences. Thus, tea based on butterfly pea flower extract offers dual benefits as a mucus solvent and bacteria inhibitor, which can be used as a natural alternative to support respiratory tract health.